Quantitative assessment of full field deformation of right ventricle during open heart surgery. Issue 2 (4th March 2021) - Soltani, A.; Lahti, J.; Järvelä, K.; Laurikka, J.; Hokka, M.
ABSTRACT: A mathematical method is introduced for quantifying full field deformation images of right ventricle (RV) of the heart. These images are acquired from the RV of the heart during open-heart surgery and analysed using digital image correlation (DIC). The high degree of complexity of the deformation of the heart, especially for the patients who require heart surgery emphasises the importance of a method to analyse the visible section of the surface of the RV. This is difficult with conventional heart-monitoring methods, which rely on describing the overall deformation of the area of interest by measuring the deformation between two points only and discarding all other relevant information contained in the area of interest. In this work, we decomposed the full field deformation images of the visible section of RV into shape descriptor vectors and used the Euclidian distance between two shape descriptor vectors obtained from the reference image and the analysed image to quantify the full field deformation by a single number. The Euclidian distance was used to compare the motion and deformation state of the heart at various stages during the operation. We demonstrate that the Euclidian distance is a more robust indicator describing the overall function of the heart than an individual strain value, especially in case of poor-quality images from which the strain is derived.